Molecular characterization & epidemiology of carbapenem-resistant Acinetobacter baumannii collected across India - Vijayakumar, Saranya (Indian J Med Res, 2019)
BACKGROUND & OBJECTIVES: Acinetobacter baumannii is an opportunistic pathogen responsible for causing nosocomial infections. A. baumannii develops resistance to various antimicrobial agents including carbapenems, thereby complicating the treatment. This study was performed to characterize the isolates for the presence of various β-lactamases encoding genes and to type the isolates to compare our clones with the existing international clones across five centres in India. METHODS: A total 75 non-repetitive clinical isolates of A. baumannii from five different centres were included in this study. All the isolates were confirmed as A. baumannii by bla(OXA-51-like) PCR. Multiplex PCR was performed to identify the presence of extended spectrum β-lactamases (ESBL) and carbapenemases. Multilocus sequence typing was performed to find the sequence type (ST) of the isolates. e-BURST analysis was done to assign each ST into respective clonal complex. RESULTS: bla(OXA-51-like) was present in all the 75 isolates. The predominant Class D carbapenemase was bla(OXA-23-like) followed by Class B carbapenemase, bla(NDM-like). Class A carbapenemase was not observed. bla(PER-like) was the predominant extended spectrum β-lactamase. ST-848, ST-451 and ST-195 were the most common STs. Eight-novel STs were identified. e-BURST analysis showed that the 75 A. baumannii isolates were clustered into seven clonal complexes and four singletons, of which, clonal complex 208 was the largest. INTERPRETATION & CONCLUSIONS: Most of the isolates were grouped under clonal complex 208 which belongs to the international clonal lineage 2. High occurrence of ST-848 carrying bla(OXA-23-like) gene suggested that ST-848 could be an emerging lineage spreading carbapenem resistance in India.